Oscillatory brain responses to emotional stimuli are effects related to events rather than states - Luther, Lisa; Horschig, Jörn M.; van Peer, Jacobien M.; Roelofs, Karin; Jensen, Ole; Hagenaars, Muriel A. (Frontiers in Human Neuroscience, 2023)
Emotional cues draw attention, thereby enabling enhanced processing. Electrophysiological brain research in humans suggests that increased gamma band activity and decreased alpha band activity over posterior brain areas is associated with the allocation of attention. However, emotional events can alternate quickly, like rapidly changing news items and it remains unknown whether the modulation of brain oscillations happens in a stimulus induced manner, changing with each individual stimulus, or whether the events lead to prolonged, state-like changes. To investigate this, we measured the electroencephalogram (EEG) during a passive viewing task (N=32) while emotional pictures (IAPS) were presented in blocks containing either pleasant and neutral or unpleasant and neutral pictures. As predicted, we found decreased alpha and increased gamma power over posterior areas in response to unpleasant compared to pleasant pictures (and also compared to neutral pictures for gamma power). When testing the neutral pictures of the unpleasant and pleasant block against each other, we found no significant difference, which speaks to a stimulus-induced effect of alpha and gamma power rather than a state effect. In addition, the inter-trial interval between the pictures did not differ between the unpleasant and pleasant block either, corroborating this conclusion. Since emotional pictures can at the same time elicit a freezing-like response and we were interested in whether this freezing-like response co-occurs with enhanced attention, we also collected postural sway data. However, within this EEG-setup, postural analyses indicated no stimulus-related effects nor a correlation with EEG-data. We interpret the alpha and gamma band results as reflecting event-related attention towards unpleasant compared to pleasant (and neutral) pictures and discuss this finding in light of previous EEG research and in combination with behavioural research on threat-induced reductions in body sway (freezing-like response).